2020
DOI: 10.1016/j.jiph.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

The outbreak of the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2): A review of the current global status

Abstract: There is currently an ongoing worldwide pandemic of a novel virus belonging to the family of Coronaviruses (CoVs) which are large, enveloped, plus-stranded RNA viruses. Coronaviruses belong to the order of Nidovirales, family of Coronavirinae and are divided into four genera: alphacoronavirus, betacoronavirus, gammacoronavirus and deltacoronavirus. CoVs cause diseases in a wide variety of birds and mammals and have been found in humans since 1960. To date, seven human CoVs were identified including the alpha-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
137
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 100 publications
1
137
0
11
Order By: Relevance
“…The severe acquired respiratory syndrome coronavirus-2 (SARS-CoV-2), the etiological agent of coronavirus disease 19 (COVID-19), is an RNA virus that induces mild to severe respiratory distress in infected individuals [ [1] , [2] , [3] ]. The disease, started from wet seafood market area of Wuhan province (China), has now affected 218 countries leading to a global pandemic threat with severe implications on healthcare system worldwide [ 4 ]. As of January 15, 2021, the SARS-CoV-2 have already infected more than 90 million people worldwide and caused about two million deaths.…”
Section: Introductionmentioning
confidence: 99%
“…The severe acquired respiratory syndrome coronavirus-2 (SARS-CoV-2), the etiological agent of coronavirus disease 19 (COVID-19), is an RNA virus that induces mild to severe respiratory distress in infected individuals [ [1] , [2] , [3] ]. The disease, started from wet seafood market area of Wuhan province (China), has now affected 218 countries leading to a global pandemic threat with severe implications on healthcare system worldwide [ 4 ]. As of January 15, 2021, the SARS-CoV-2 have already infected more than 90 million people worldwide and caused about two million deaths.…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel beta-coronavirus that has caused a global outbreak of respiratory disease, Coronavirus Disease 2019 (COVID-19), with significant morbidity, mortality, and excess healthcare costs [ 1 , 2 ]. An important aspect of controlling and slowing the spread of this pandemic is the availability of reliable and accurate methods for testing both symptomatic and asymptomatic individuals [ [3] , [4] , [5] ].…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory approvals in Asia accounted for nearly 34% of the total number of approvals granted. Experts have suggested that the high proportion of approvals in this region may be due to the rigorous COVID-19 testing strategies implemented to contain the spread of the infection [ 7 , 59 , 64 , 68 , 75 , 103 , 104 ]. The number of CE (Conformité Européene) marked diagnostic technologies in Europe accounted for 29.5%.…”
Section: Resultsmentioning
confidence: 99%